The Growth of Digital Payments in Indonesia: Harnessing Its Influence for SMEs and Indonesia's Competitiveness - Maharsi, Hayuningrum Citra (Global South Review, 2024)
Digital Payment System (DPS) growth plays a crucial role in supporting the country's digital economic growth. As a country representing the global south, Indonesia has an important responsibility to manage the dynamics of DPS growth, which is influenced significantly by actors from the government and private sectors. Initially, DPS was designed to provide more efficient and accessible payment services, but over time, the scope of such digital services has expanded. Nevertheless, challenges must be addressed in distributing DPS evenly, especially among MSMEs. Through the approach promoted by the Economic Asian Committee (EAC), this study aims to assess the impact of DPS growth on the digital services ecosystem in Indonesia and the dynamics of interaction between related stakeholders. Qualitative methods are used to summarize information from various sources, including journal literature and data from websites, which provide an in-depth understanding of the complexity of this phenomenon and Indonesia's efforts to improve its overall digital competitiveness. The findings in this study indicate that the Digital Payment System (DPS) offers numerous benefits for the financial system, enhancing efficiency and effectiveness for industrial growth. However, challenges in ensuring equitable usage across all regions of Indonesia remain significant across various sectors.  Keywords: digital payment system; global south actor; MSMEs; digital competitiveness of Indonesia